Editorial [Hot Topic: Gout (Guest Editor: Tony R. Merriman)] - R. Merriman, Tony (Current Rheumatology Reviews, 2011)
This Hot Topic issue focuses on gout, for the first time in Current Rheumatology Reviews. The pathogenesis of gout encompasses many pathways, all of relevance for prevention and treatment, all with genetic and environmental risk factors, including but not limited to, production of urate in the blood, renal urate transport, monosodium urate crystal formation, activity of the inflammasome, bone erosion and the relationship with the metabolic syndrome. Collectively, the nine review articles in this issue take a broad-brush approach to reviewing gout. Gout is not only a manifest form of arthritis, but it's etiology is inter-twined with the metabolic syndrome, a constellation of metabolic perturbations (dyslipidemia, hypertension, insulin resistance, central adiposity, renal disease) that increase the risk of cardiovascular disease and type 2 diabetes. Common risk factors, both environmental and genetic, are likely to be shared by this suite of metabolic disorders. The relationship of hyperuricaemia and gout with the metabolic syndrome is a thread linking many of the articles in this Hot Topic issue. A second commonality will be revealed at the end of this editorial. The issue begins with an article by Taylor [1] on current procedures for the diagnosis of gout, comparatively straightforward when based upon the identification of monosodium urate crystals in synovial fluid. However this is not always practical, meaning that classification criteria are required in clinical research, whereas in clinical practice additional factors can be considered. The article describes the potential of ultrasound as a diagnostic tool. Classification of gout is important as suboptimal classification does impact on the power of clinical research [2]. The next two articles paint a picture of the interaction of environmental and genetic risk factors in gout. Buckley [3] describes paleopathological evidence for a higher incidence of gout in ancient Pacific cultures than in past European cultures. Over the past century the incidence of gout in these populations has increased in response to a changing environment but with a parallel dichotomy, with Polynesian populations now exhibiting the highest prevalence worldwide. Historically, gout was associated with individuals of higher status whereas there is no such distinction now. Fructose is a very strong candidate environmental risk factor, raising serum urate levels as a consequence of it's catabolism and perhaps by interfering with renal uric acid excretion. Gene association studies, described by Merriman and Dalbeth [4], show that genetic variation in urate transporters (such as SLC2A9 and ABCG2) control serum urate levels and influence the risk of gout in diverse populations. The epidemiological and genetic data are consistent with fructose and other environmental factors (such as obesity and purinerich food) raising serum urate levels, which is exacerbated in people with genetic variants that reduce urate excretion, thus increasing the risk of gout. An intriguing association between serum urate levels and the glucokinase regulator gene suggests a possible genetic link between gout, dyslipidemia and diabetes. Two articles focus on key regulatory steps in gout, namely renal urate transport and the inflammasome [5,6]. As described by Anzai et al. [5], the previous ten years has seen the identification and characterisation of several renal urate transporters, including the kidney-specific URAT1 (SLC22A12) and several organic anion transporters, whereas genetic approaches have identified the urate transporters SLC2A9 and ABCG2 [4]. Collectively, these and other molecules, are referred to as the urate ‘transportasome’, a molecular machine central to gout and other disorders of urate metabolism. The development of unique mouse lines, with tissue-specific expression of urate transporters is allowing the dissection of the transportasome, in a fashion not possible in humans. The gout ‘NALP3’ inflammasome is the subject of the review by Guarda et al. [6]. This inflammasome is another molecular machine in the innate immune system that responds to signals initiated by urate crystals. The inflammasome produces mature interleukin-1β, triggering an inflammatory cascade that culminates in a painful but self limiting acute attack of gout. Intriguingly, the NALP3 inflammasome has very recently been shown to be activated by cholesterol crystals [7], suggesting a possible link between gout and dyslipidemia. The article by Stamp and Chapman [8] reviews current clinical practice in management of gout. Central to clinical practice is an accurate diagnosis and treatment of the acute attack, followed by a urate-lowering therapy (typically allopurinol, that inhibits the production of urate in the blood) alongside adequate prophylaxis against acute gout attacks during the introduction of the urate-lowering therapy. Promising for the management of acute attacks are biologics that inhibit the action of interleukin- 1β. The potent but not widely available drug benzbromarone, that stimulates renal urate excretion, will retain a role in patients with renal impairment. The interleukin-1β biologics and benzbromarone target the product of the inflammasome and renal urate transportasome, respectively, emphasizing the importance to gout of these molecular machines [6,7]. Chhana and Dalbeth [9] discuss mechanisms of bone erosion in chronic gout, a source of disability when gout is poorly managed. Owing to the paucity of research in this area, they draw on knowledge of the processes of bone erosion in other more heavily researched arthropathies (for example, rheumatoid arthritis and wear debris-induced osteolysis). Therapies targeting the osteoclast show promise, but research in this area is hindered by the absence of a suitable animal model of tophaceous gout. The penultimate article directly addresses the relationship of hyperuricemia with the metabolic syndrome. Lanaspa et al. [10] point out that elevated uric acid was considered a part of the metabolic syndrome in the early part of the twentieth century, when diabetes was rare. However, elevated uric acid is no longer considered part of the metabolic syndrome. In recent decades the relationship between uric acid, gout and the metabolic syndrome has again come under the spotlight, with the key question: ‘Is uric acid causal or a consequence of the metabolic syndrome?’ Lanaspa et al. [10] address this question, concluding that the answer is ‘both of the above’. Important in considering the relationship between hyperuricemia and metabolic syndrome is the context of action of uric acid - is it influencing oxidative stress within the cell? Is it acting as a proinflammatory molecule? Is it having vasoactive effects? The role of fructose in these processes is also evaluated by Lanaspa et al. [10]. Lanaspa et al. [10] sensibly focused on hyperuricemia and metabolic syndrome and did not address the relationship with gout per se, where associated localized and systemic inflammation may prove to add an extra dimension to the relationship with metabolic syndrome. As Stamp and Chapman [8] emphasise, we need to integrate gout management with treatment of metabolic comorbidities. This approach will require a sound evidence base, derived from multidisciplinary and longitudinal research, including molecular understanding of the role of the environment in the pathogenesis of gout and co-morbidities.....